A population based study of intracranial arachnoid cysts: clinical and neuroimaging outcomes following surgical cyst decompression in adults. Issue 10 (13th February 2007) - Helland, Christian A; Wester, Knut
Abstract : Background: We have gradually adopted a liberal attitude towards surgical decompression of arachnoid cysts. This study describes the results from our institution. Methods: Long term clinical and neuroimaging results of 156 adult patients (aged ⩾16 years) operated on for arachnoid cysts in our department during the period January 1987 to September 2004 were assessed based on their medical and neuroimaging records, and on a questionnaire. Results: The clinical and/or neuroimaging results indicated that the cyst was successfully decompressed in all patients. 82% of patients were asymptomatic or had insignificant complaints at follow-up. 12% reported no symptom relief whereas 6% experienced worsening of symptoms. The cyst disappeared after surgery, or was reduced to <50% of the preoperative volume, in 66% of cases. In another 24%, the postoperative volume was also reduced, but was larger than 50% of the original cyst volume. No reduction in fluid volume was observed in 10% of cases. There was no association between volume reduction and clinical improvement. A complication occurred in 26 patients (17%), all with temporal cysts, leading to reoperation in 11 patients (7.1%). In only two patients did the complication cause a permanent slight disability. Conclusion: Decompression of arachnoid cysts yields a substantial clinical benefit with a low risk of severe complications.